PENGELOLAAN KEUANGAN DAN PENCATATAN UTANG PADA USAHA MIKRO DALAM PERSPEKTIF EKONOMI SYARIAH - Endang Purnamawati; Reza Okva Marwendi; Kurniawan (Swakarya: Jurnal Penelitian Sosial dan Pengabdian Masyarakat, 2025)
The purpose of this research is to determine how to manage finances and record consumer and producer debt in wholesale and retail businesses. Seventh-semester students are strongly encouraged to participate in field experience activities to develop ideas for small sample projects before delving into more in-depth research, such as a thesis. In this research, methods for solving problems such as financial management require business owners to be disciplined in setting aside savings and investments, building an emergency fund, and avoiding consumer debt. Regarding debt recording, business owners must provide deadlines or timeframes for consumers to repay their debts in installments or cash. Through these field experience activities and community service, students can share their knowledge, technology, and art with the community. In wholesale and retail businesses, there are often cases of goods not matching the records or purchase orders with agents, unclear accounts receivable and accounts receivable are often recorded, and fraud and dishonesty often occur among both consumers (buyers) and producers (sellers). Therefore, all activities in these businesses should be managed properly and correctly to avoid losses.